Disaster Response Self-Efficacy of Students in the Nursing Department: A Cross-Sectional Study - Dilek Yılmaz; Gonca Buran (Makara Journal of Health Research)
Background: Nurses take on important roles in disasters. In this regard, the disaster response self-efficacy of nursing students must be evaluated. The study aimed to determine the self-efficacy of nursing students in disaster response.